BIOGRAPHY AND CONTRIBUTION TO SCIENCE OF ACADEMICIAN. TSEGMID SHAGDAR (1922-2004), THE FOUNDER OF THE GEOGRAPHIC SCIENCE IN MONGOLIA AND THE STATE AWARD RECIPIENT (Mongolian Journal of Geography and Geoecology, 2022)
МОНГОЛД ГАЗАРЗҮЙН ШИНЖЛЭХ УХААНЫГ ҮНДЭСЛЭГЧ, ТӨРИЙН ШАГНАЛТ, АКАДЕМИЧ ШАГДАРЫН ЦЭГМИД АГСНЫ НАМТАР, ШИНЖЛЭХ УХААНД ОРУУЛСАН ХУВЬ НЭМЭР (1922-2004)